Epidemiological characteristic of rubella by age group during 12 years after the national introduction of rubella vaccine in Hangzhou, China - Jun Wang; Yuyang Xu; Xiaozhen Wang; Yan Liu; Xiaoping Zhang; Jian Du; Xinren Che; Wenwen Gu; Xuechao Zhang; Wei Jiang; Yi Wang (Taylor & Francis Group, 2022)
This study aimed to evaluate the implementation and impact of rubella-containing vaccine (RCV) by describing the rubella epidemiology and seroepidemiology in Hangzhou. We collected rubella cases of Hangzhou in the Information System for Disease Control and Prevention in China between 2009 and 2020, and performed a descriptive analysis. We applied a multi-stage stratified random sampling method to recruit participants for serological tests of rubella. Enzyme Linked Immunosorbent Assay (ELISA) was used to detect Immunoglobulin G (IgG) antibodies against rubella in serum samples. Univariate and multivariate analyses are used to detect the association between the level of rubella IgG and related factors. The incidence of rubella cases per million population decreased from 15.8 in 2009 to .1 in 2020. The proportion of rubella cases in women of childbearing age was higher than in men. A total of 4,362 subjects were tested serologically for rubella. The percentage of people whose rubella IgG antibody titers were above the minimum protective level (20 IU/ml) was 80.60% (95% CI: 79.4%-81.8%) and the geometric mean concentration (GMC) for rubella IgG was 58.34 IU/ml. The data indicated that Hangzhou had made good progress toward the elimination of rubella, whereas women of childbearing age still had a higher proportion of rubella cases, which might lead to increased risk of subsequent CRS. The positive rate and GMC of rubella IgG were significantly influenced by age and immunization history of RCV. Therefore, we should stress the importance of pushing forward the campaign for supplementary vaccination of rubella in adults.